Missed nursing care, nurse staffing levels and patient safety outcomes in low‐income country acute care settings: An observational study. Issue 1 (30th December 2021) - Assaye, Ashagre Molla; Wiechula, Richard; Schultz, Timothy J.; Feo, Rebecca
Abstract: Aims: The aim of this study was to measure the level of missed nursing care and determine its relationship with nurse staffing and patient safety outcomes in acute care settings in Ethiopia. Background: Missed nursing care in hospitals increases the likelihood of patient adverse events, complications, disability and death. However, little is known about the level of missed nursing care and its impact on patient outcomes in low‐income countries. Methods: An observational study was conducted comprising of a survey of nurses at two time points ( n  = 74 and 80, respectively) and a medical record review of 517 patients in four units across two hospitals between September 2018 and March 2019. Results: The level of missed nursing care in the study units was very high. The hospital type and hours nurses worked during the last week were significantly associated with missed nursing care. A unit increase in missed nursing care score increased the incidence of adverse patient outcomes by 10%. Conclusion: There was a higher level of missed nursing care in the study units compared with similar studies from high‐income countries. Higher level of missed nursing care was significantly associated with higher incidence of adverse patient safety outcomes. Summary statement: What is already known about this topic? Literature shows nurses working in acute care miss important nursing care activities mainly due to lack of time to perform those nursing care activities. What this paper adds? The level of missed nursing care in the low‐income country acute care units of the study hospitals is very high compared with other settings. Higher levels of missed nursing care were statistically associated with increase adverse patient safety outcomes, whereas lower levels of missed nursing care were statistically associated with improved patient outcomes. The implication of this paper Hospital administrators and nurse managers should work towards reducing missed nursing care through regular monitoring of nursing practice and improved staffing levels. Mechanisms to improve staffing and resource are required to enable nurses enough time to perform all essential nursing care activities for patients.